Synthesis of constrained analogues of tryptophan - Rossi, Elisabetta; Pirovano, Valentina; Negrato, Marco; Abbiati, Giorgio; Dell’Acqua, Monica (Beilstein Journal of Organic Chemistry, 2015)
A Lewis acid-catalysed diastereoselective [4 + 2] cycloaddition of vinylindoles and methyl 2-acetamidoacrylate, leading to methyl 3-acetamido-1,2,3,4-tetrahydrocarbazole-3-carboxylate derivatives, is described. Treatment of the obtained cycloadducts under hydrolytic conditions results in the preparation of a small library of compounds bearing the free amino acid function at C-3 and pertaining to the class of constrained tryptophan analogues.
Keywords: constrained tryptophans; Diels–Alder; indoles; tetrahydrocarbazoles; unnatural amino acids